Reframing Hijab and Public Morality: Gender Justice through Maqāṣid and Qirā’ah Mubādalah - Wahyu Elvita Rohmi; Almughni Mika (Zamzami Scholar Publishing, 2026)
The discourse on the hijab in the contemporary context is no longer limited to a symbol of individual piety but has developed into an arena of identity contestation fraught with politicization, stereotypes, and discriminatory practices in the public sphere. This article examines these dynamics through a netnographic analysis of the Instagram account @lia_lestari29, which represents resistance to symbolic coercion, and then analyzes them through a synthesis of Quraish Shihab’s thoughts and the Qirā’ah Mubādalah approach. The results of the study show that the integration of legal flexibility based on maqāṣid al-sharī‘ah with the hermeneutics of reciprocity is capable of reconstructing textual readings that tend to be gender biased, particularly in the interpretation of the hadith kasiyāt ‘āriyāt. This study emphasizes that the construction of public morality should not be imposed exclusively on women, but rather be positioned as a collective ethical responsibility that binds men and women equally. Thus, the recontextualization of dress ethics based on the principles of al-ḥayā’ and gender justice is a prerequisite for the establishment of an inclusive, democratic social order that is free from structural exclusion.